Weakly Coupled Systems of Semilinear Damped Waves with Different Scale-Invariant Time-Dependent Dissipation Terms - Abdelhamid Mohammed Djaouti (Journal of Mathematics)
In this paper, our interest is the global existence of small data solutions to the Cauchy problem for weakly coupled systems of semilinear damped waves with different scale-invariant dissipation terms, where the data are supposed to belong to different classes of regularity and different power nonlinearities.